2011
DOI: 10.5902/198050984517
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento populacional e análise faunística de lepidoptera em <i>Eucalyptus </i>spp. no município de Pinheiro Machado, RS

Abstract: O trabalho teve como objetivo coletar, identificar e caracterizar faunisticamente os lepidópteros associados a um plantio de Eucalyptus spp., no município de Pinheiro Machado, RS. No período de outubro de 2005 a outubro de 2007, a cada 15 dias, foram realizadas coletas de insetos com três armadilhas luminosas instaladas no interior do florestamento. Após procedimentos de triagem, transfixação e montagem os lepidópteros foram identificados comparando-os a coleções entomológicas e com uso de literatura especiali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
(4 reference statements)
0
18
0
3
Order By: Relevance
“…The available data about the immature stages of cutworm species (e.g., Specht 1972 , Link and Kies 1973, Angulo and Weigert 1975 , Bryan et al 2000 , Baudino 2004 , Corró Molas et al 2017 ) and adults collected by light traps (e.g., Hills 1968 , Tarragó et al 1975 , Lara et al 1977 , Lara and Silveira Neto 1977 , Silveira Neto et al 1977 , Specht and Corseuil 2002 , Specht et al 2005 , Zenker et al 2010 , Bernardi et al 2011 ) indicate spatial and temporal variations of the species as a function of climate conditions, available crops, and insect management. Therefore, a local assessment of cutworm species and their host plants is recommended to avoid yield loss, particularly due to the stand reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The available data about the immature stages of cutworm species (e.g., Specht 1972 , Link and Kies 1973, Angulo and Weigert 1975 , Bryan et al 2000 , Baudino 2004 , Corró Molas et al 2017 ) and adults collected by light traps (e.g., Hills 1968 , Tarragó et al 1975 , Lara et al 1977 , Lara and Silveira Neto 1977 , Silveira Neto et al 1977 , Specht and Corseuil 2002 , Specht et al 2005 , Zenker et al 2010 , Bernardi et al 2011 ) indicate spatial and temporal variations of the species as a function of climate conditions, available crops, and insect management. Therefore, a local assessment of cutworm species and their host plants is recommended to avoid yield loss, particularly due to the stand reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the economy of Misiones is structured around forestry production and that plantation of Eucalyptus spp. is used for lumber and pulp production [48], we highlight that Bernardi et al [72] have already shown that L. obliqua larvae are defoliators of the eucalypts, as well as other plantations, resulting in pest outbreaks [68]. Hence, monitoring the…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 94%
“…Temperature and humidity are the main environmental factors that influence occurrence, distribution and complete development of M. latipes biological cycle. Therefore, the imbalance of these conditions directly interferes in population size (Bertels 1970, Bernardi et al 2011. Understanding spatial and temporal distribution of pest species is important to reduce risks of Outbreaks and to develop sustainable management control (Pedigo & Rice 2009).…”
Section: Introductionmentioning
confidence: 99%